Chromosomal Microarray in Children With Developmental Delay: The Experience of a Tertiary Center in Korea - Yang, Eun Hye; Shin, Yong Beom; Choi, Soo Han; Yoo, Hye Won; Kim, Hye Young; Kwak, Min Jung; Park, Kyung Hee; Bae, Mi Hye; Kong, Ju Hyun; Lee, Yun-Jin; Nam, Sang Ook; Kim, Young Mi (Frontiers in Pediatrics, 2021)
Background and objectives. Chromosomal microarray (CMA) is a first-tier genetic test for children with developmental delay (DD), intellectual disability (ID), autism spectrum disorders (ASDs), and multiple congenital anomalies (MCA). In this study, we report our experiences with the use of CMA in Korean children with unexplained DD/ID. Methods: We performed CMA in a cohort of 308 children with DD/ID between January 2010 and September 2020. We also retrospectively reviewed their medical records. The Affymetrix CytoScan 750K array with an average resolution of 100 kb was used to perform CMA. Results: Comorbid neurodevelopmental disorders were ASD (37 patients; 12.0%), epilepsy (34 patients; 11.0%), and attention deficit hyperactivity disorders (12 patients; 3.9%). The diagnostic yield was 18.5%. Among the 221 copy number variants (CNVs) identified, 70 CNVs (57 patients; 18.5%) were pathogenic. Deletion CNVs were more common among pathogenic CNVs (PCNVs) than in non-PCNVs (P<0.001). The size difference between PCNVs and non-PCNVs was not significant (P=0.023). The number of included genes within CNV intervals was significantly higher in PCNVs (average 8.6; 0–347) than in non-PCNVs (average 47.5; 1–386) (P<0.001). Short stature and hearing difficulty were also more common in the PCNV group than in the non-PCNV group (P=0.010 and 0.070, respectively). Conclusion: This study provides additional evidence for the usefulness of CMA in genetic testing of children with DD/ID in Korea. The pathogenicity of CNVs correlated with the number of included genes within the CNV interval and deletion type of the CNVs, but not with CNV size.